Accumulation of tumor-suppressor PTEN in Alzheimer neurofibrillary tangles - Sonoda, Yuma; Mukai, Hideyuki; Matsuo, Kazuhiko; Takahashi, Mikiko; Ono, Yoshitaka; Maeda, Kiyoshi; Akiyama, Haruhiko; Kawamata, Toshio (Neuroscience letters, 2010)
The phosphatase and tensin homologue deleted on chromosome 10 (PTEN) negatively regulates intracellular levels of PIP3 and antagonizes the PI3K signaling pathway important for cell survival. The present study determined whether altered distribution of PTEN occurs in Alzheimer's disease (AD) brains. We investigated a possible role for PTEN in postmortem brain tissues from elderly controls and patients with AD using immunoblotting and microscopic analyses. Intense immunolabeling was found in the large neurons such as pyramidal cells. In normal neurons, PTEN was located in the nucleus, the cytoplasm of cell bodies and the proximal portion of apical dendrites. Reduced expression and redistribution of PTEN was seen in the remaining neurons in AD. In addition, PTEN was redistributed in damaged neurons from the nucleus and cytoplasm to neuritic pathology such as intracellular neurofibrillary tangles (NFTs), neuropil threads and dystrophic neurites within senile plaques in AD hippocampus, subiculum, entorhinal cortex and angular gyrus. Furthermore, double immunofluorescence staining showed dual labeling of intracellular NFTs for PTEN and tau, labeling of some axons for PTEN and phosphorylated neurofilament, and weak labeling of a few reactive astrocytes around senile plaques for PTEN and GFAP. Double labeling of NFTs was observed in a subset of tangle-bearing neurons either for PTEN and GSK3β or for PTEN and MEK. Thus our results suggest that PTEN delocalized from the nucleus to the cytoplasm and to intracellular NFTs may cause a deregulation of PI3K pathway in the cytoplasm and may induce the nuclear dysfunction of PTEN in AD degenerating neurons.